Pajak Penghasilan Badan Dipengaruhi Oleh Tax Planning Dan Leverage Dengan Manajerial Ownership Sebagai Variabel Moderating - Srikalimah Srikalimah; Ahmad Yani; Fiki Chusniatus Sa’adah (Owner : Riset dan Jurnal Akuntansi, 2023)
The banking sector is a service sector company that is expected by the central government to be able to work stably and also provide good income for the government with the income tax deposited. The existence of tax planning and leverage practices by companies will tend to reduce the income tax that will be paid by the company. This study aims to find out whether the company in carrying out its activities already carries out tax planning and also leverage to reduce the amount of income tax tax.This research is a descriptive study with a quantitative approach with the aim of analyzing, explaining, and concluding regarding the effect of tax planning and leverage on corporate income tax. The data collection technique in this study is in the form of documentation of the financial statements of banking sector companies listed on the IDX 2019-2021. The analysis technique used in this study is in the form of Classical Assumption Test, Multiple Linear Regression Test and Hypothesis Test. The results of this study indicate that tax planning has no partial positive effect on Corporate Income Tax. The leverage variable has a partially significant negative effect on Corporate Income Tax. While the simultaneous effect shows that the leverage and tax planning variables simultaneously influence Corporate Income Tax.